Development of Efficient and Environmentally Friendly Septic Tanks - Brian Alfandi; M. Ali Mukmin; Ria Rosyati; Siti Abadiyah (LPPM Universitas Negeri Jakarta, 2024)
In many communities in Indonesia, there are still many areas where their homes do not have a toilet (water closet) that meets hygiene and health requirements. This is caused by many factors, including because there are still many people who live below the poverty line, both economically poor and poor in knowledge (human resources). Procurement of toilets (water closets) which also include a septic tank system with a minimum output that is environmentally friendly and of course cost efficient is very necessary to improve public health. Based on the description above, this research was created in order to provide procurement and development of efficient and environmentally friendly septic tanks. This research is very necessary because of the discovery of an efficient alternative material by using used drums which can be used as septic tanks in Lampung, but it has not deepened the issue of waste output that is safe for the environment. This research was carried out using a constructivist qualitative method with assistance from DIGILIB Digital Library & OPAC UB sources. is at Brawijaya University Malang, where the author is registered as a student in the environmental science doctoral program at Brawijaya University Malang.